Evaluation of Mechanical Behaviour Aluminium Metal Matrix Composites - Gunasekaran, D.; Parthasarathy, C.; Chandradass, J. (Asian Journal of Engineering and Applied Technology, 2015)
Technology is advancing, demand of the hour is increasing and to face that engineers are also ready. Maintaining the economic production with optimal use of resources is of prime concern for the engineers. Aluminum alloy materials or simply composites are combinations of materials. They are made up of combining two or more materials in such a way that the resulting materials have certain design properties on improved properties .The Aluminum alloy composite materials consist of high specific strength, high specific stiffness, more thermal stability, more corrosion and wear resistance, high fatigue life. Conventional materials like Steel, Brass, and Aluminum etc will fail without any indication. Cracks initiation, propagation will takes place within a short span. Now a day to overcome this problem, conventional materials are replaced by Aluminum alloy materials. Aluminum alloy materials found to the best alternative with its unique capacity of designing the materials to give required properties. In this project tensile strength experiments have been conducted by varying mass fraction of SiC and fly ash magnesium with Aluminum. To attain maximum tensile strength various mechanical properties alloys are also to be investigated.